Photosynthetic CO2 uptake by microalgae: An attractive tool for biogas upgrading. (February 2015) - Meier, L.; Pérez, R.; Azócar, L.; Rivas, M.; Jeison, D.
Abstract: The use of photosynthetic CO2 reduction capacity of microalgae can be used for biogas upgrading. Such process would convert CO2 contained in the biogas into microalgal biomass, generating two products: upgraded biogas and biomass. Growth rate of Nannochloropsis gaditana was determined in atmospheres containing different levels of CH4 and CO2 . Results showed no effect of CH4 rich atmosphere over microalgal development. CO2 inhibition was observed only when microalgae culture was exposed to atmospheres containing 9% of CO2 . Direct contact of the biogas and the microalgal culture is not a feasible way to upgrade biogas, due to oxygen desorption to the gas phase. A two-stage process, involving a photobioreactor connected with a gas/liquid mass transfer unit showed to be an efficient way to remove CO2 from the biogas, keeping low levels of oxygen in the upgraded biogas. Graphical abstract: Highlights: Microalgae represent an attractive tool for transforming biogas into biomethane. Atmospheres with high CH4 content do not affect the growth of Nannochloropsis gaditana. Biogas upgrading with algae requires uncoupling CO2 absorption from O2 desorption. Photo-bioreactor-bubble column system is proposed and tested for biogas upgrading.